ULAMA'S POLITICAL STRUGGLING IN STRENGTHENING WASATHIYAH ISLAM IN THE PALACE - Pagar, Pagar; Akhyar, Syaiful (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
The magnitude of the ulema's obsession to color power in Indonesia is reflected in the fierceness of their battle in the 2019 presidential election. The direct involvement of the ulama made this political event special and different from the previous presidential elections throughout Indonesian history. What's special about this event is that it started from the views of scholars; "We must participate in determining the direction of this nation's journey, so that it is guaranteed that the Islamic perspective of wasathiyah is implemented in it, to be able to realize this effectively, we must color Indonesia from within, by appearing as a policy maker". To implement this, the ulama have been divided into two types of religious understanding which incubated into a political movement and were affiliated with the two presidential candidate pairs. Each of them struggles in their own way, including; The 212 mass movement which was very monumental and fantastic by the Ulama, while on the other hand, had advanced to become a candidate for Vice President from the top leadership of the Ulama in Indonesia, both in terms of the MUI Ormas (as a forum for the gathering of ulama and zu'ama). also from the NU mass organization (as the largest religious mass organization in Indonesia), namely KH. Ma`ruf Amin who is the chairman. Finally, it is reflected that the presidential election battle this time is not only a battle for the presidential seat in the palace, but also as a political battle with the religious style of the ulama to color the throne of power in Indonesia, namely, Wasathiyah Islam and Exclusive Islam. It turns out that the religious style of Wasathiyah Islam as the original inhabitants of this nation can still be victorious in this battle, as well as strengthen the existence of the state in a form that is nationalist Pancasila so that the citizens of the state live in peace in diversity and plurality. Keywords: Ulama, Wasathiyah Islam, Struggling of Islam